1989
DOI: 10.1093/jac/24.suppl_b.111
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics of ticarcillin/clavulanate acid in neonates

Abstract: The pharmacokinetics of a 25:1 combination of ticarcillin and clavulanate were studied in nine pre-term and seven full-term neonates. Pre-term neonates with a gestational age ranging from 30 to 36 weeks received 83.3 mg of ticarcillin and 3.3 mg of clavulanate per kg bw and full-term neonates with a gestational age from 39 to 43 weeks received 100 mg of ticarcillin and 4 mg of clavulanate per kg bw 8-hourly, each by a slow infusion over 10 min. Serum was sampled 15, 30, 60, 120, 240 and 480 min after the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 0 publications
2
17
1
Order By: Relevance
“…Retrospective analysis by optimal sampling theory (5, 6,8) The pharmacokinetic parameters that we determined were consistent with those reported by other investigators (9,12) in infants closer to full term than ours,, Fayed et al (9) reported a mean ± standard deviation t1,2 for ticarcillin of 4.5 ± 3.4 h and for clavulanic acid of 2 ± 1.6 h. Their sample consisted of 24 newborn infants with a mean gestational age of 30.7 weeks (range, 25 to 39 weeks) and a mean birth weight of 1,700 g (ranige, 895 to 3,900 g) (9). Fricke et al (12), in their sample of seven preterm infants with a mean birth weight of 2,377 g (range, 1,915 to 2,650 g) and a mean gestational age of 35 weeks (range, 34 to 36 weeks), found a mean ± standard deviation Vs, and t12 for ticarcillin of 0.338 ± 0.35 liter/kg and 4.20 ± 0.50 h, respectively and for clavulanic acid of 0.414 + 0.29 liter/kg and 2.56 + 0.18 h, respectively. Additionally, the pharmacokinetics of ticarcillin and clavulanic acid were available for one patient with a gestational age of 30 weeks and a birth weight of 1,400 g. The Vss and t1l2 for ticarcillin were 0.515 liter/kg and 16 h, respectively, and those for clavulanic acid were 0.441 liter/kg and 2.5 h, respectively, in that subject (12).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Retrospective analysis by optimal sampling theory (5, 6,8) The pharmacokinetic parameters that we determined were consistent with those reported by other investigators (9,12) in infants closer to full term than ours,, Fayed et al (9) reported a mean ± standard deviation t1,2 for ticarcillin of 4.5 ± 3.4 h and for clavulanic acid of 2 ± 1.6 h. Their sample consisted of 24 newborn infants with a mean gestational age of 30.7 weeks (range, 25 to 39 weeks) and a mean birth weight of 1,700 g (ranige, 895 to 3,900 g) (9). Fricke et al (12), in their sample of seven preterm infants with a mean birth weight of 2,377 g (range, 1,915 to 2,650 g) and a mean gestational age of 35 weeks (range, 34 to 36 weeks), found a mean ± standard deviation Vs, and t12 for ticarcillin of 0.338 ± 0.35 liter/kg and 4.20 ± 0.50 h, respectively and for clavulanic acid of 0.414 + 0.29 liter/kg and 2.56 + 0.18 h, respectively. Additionally, the pharmacokinetics of ticarcillin and clavulanic acid were available for one patient with a gestational age of 30 weeks and a birth weight of 1,400 g. The Vss and t1l2 for ticarcillin were 0.515 liter/kg and 16 h, respectively, and those for clavulanic acid were 0.441 liter/kg and 2.5 h, respectively, in that subject (12).…”
Section: Discussionsupporting
confidence: 84%
“…Fricke et al (12), in their sample of seven preterm infants with a mean birth weight of 2,377 g (range, 1,915 to 2,650 g) and a mean gestational age of 35 weeks (range, 34 to 36 weeks), found a mean ± standard deviation Vs, and t12 for ticarcillin of 0.338 ± 0.35 liter/kg and 4.20 ± 0.50 h, respectively and for clavulanic acid of 0.414 + 0.29 liter/kg and 2.56 + 0.18 h, respectively. Additionally, the pharmacokinetics of ticarcillin and clavulanic acid were available for one patient with a gestational age of 30 weeks and a birth weight of 1,400 g. The Vss and t1l2 for ticarcillin were 0.515 liter/kg and 16 h, respectively, and those for clavulanic acid were 0.441 liter/kg and 2.5 h, respectively, in that subject (12).…”
Section: Discussionmentioning
confidence: 99%
“…Those studies that have been carried out show that both GA and PNA have an impact on clearance and hence plasma t ½ [5,11,12,15,17,20,27,29]. Most of these PK studies have been classical PK studies where several blood samples were taken from each infant.…”
Section: Discussionmentioning
confidence: 99%
“…There have been three PK studies of ticarcillin in neonates where it has been given in combination with clavulanic acid Values are given as the mean or range Values are given as the mean or range a Patients on cardiopulmonary bypass [26][27][28] (Table 7). The first study looked at the use of prophylactic ticarcillin and clavulanic acid (ratio 15:1) in neonates from 25 to 39 weeks GA. As well as studying the PK of ticarcillin, these researchers also looked at the PK of clavulanic acid [26].…”
Section: Ticarcillinmentioning
confidence: 99%
See 1 more Smart Citation